PERFORMANCE OF BROILER CHICKENS FED MANNAN OLIGOSACCHARIDES AS ALTERNATIVES TO ANTIBIOTICS FROM ONE TO TWENTY-TWO DAYS OF AGE - Z. Kamran; M. A. Mirza; S. Ahmad; H. A. Samad; M. U. Sohail; M. Saadullah (Journal of Animal and Plant Sciences, 2013)
The present study was planned to evaluate the efficacy of mannan oligosaccharides (MOS) as alternatives to antibiotic growth promoters (AGP) in broiler diets from one to 22 days of age. A total of 200 day-old Hubbard broiler chicks were randomly divided into 20 experimental units of 10 chicks each. A basal diet was formulated containing 21% CP with 2750 kcal/kg ME. The treatment 1 contained basal diet without any supplementation. In treatments 2, 3, 4 and 5, the basal diet was supplemented with MOS (1 kg/ton of feed), zinc bacitracin 10% (0.5 kg/ton of feed), furazolidone (0.1 kg/ton of feed) and enramycin (0.12 kg/ton of feed), respectively. Each experimental diet was assigned randomly to 4 replicate pens. Results showed that feeding of either MOS or any of the AGP did not significantly affect the feed intake of birds. The weight gain and feed conversion ratio of birds fed MOS diet were superior (P<0.05) to those of control group while inferior (P<0.05) to all of AGP fed groups. However, weight gain and feed conversion ratio were not significantly different among birds fed diets containing various AGP. Mortality was also non-significant among dietary treatments. Economic evaluation of the growth data showed that use of AGP in feed was more cost effective as compared to other groups. In conclusion, the use of MOS in broiler starter diets was not found to replace AGP commonly used in feed.
Keywords: Broilers; mannan oligosaccharides; antibiotic growth promoters; growth performance